2018
DOI: 10.3390/rs10121879
|View full text |Cite
|
Sign up to set email alerts
|

Performance of TRMM TMPA 3B42 V7 in Replicating Daily Rainfall and Regional Rainfall Regimes in the Amazon Basin (1998–2013)

Abstract: Knowledge and studies on precipitation in the Amazon Basin (AB) are determinant for environmental aspects such as hydrology, ecology, as well as for social aspects like agriculture, food security, or health issues. Availability of rainfall data at high spatio-temporal resolution is thus crucial for these purposes. Remote sensing techniques provide extensive spatial coverage compared to ground-based rainfall data but it is imperative to assess the quality of the estimates. Previous studies underline at regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…Daily TRMM‐3B42 Version 7 rain estimates (3B42) have been chosen because they represent the best available daily and monthly precipitation maps in South America (Michot et al, ), as daily 3B42 rain estimates are rain gauge adjusted (bias removal). For this study, the quarter degree 3B42 spatial resolution has been averaged for an area of 1 × 1° of longitude and latitude.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Daily TRMM‐3B42 Version 7 rain estimates (3B42) have been chosen because they represent the best available daily and monthly precipitation maps in South America (Michot et al, ), as daily 3B42 rain estimates are rain gauge adjusted (bias removal). For this study, the quarter degree 3B42 spatial resolution has been averaged for an area of 1 × 1° of longitude and latitude.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Moreover, TRMM Multi-satellite Precipitation Analysis (TMPA) combined the data from TRMM-PR, VIRS, TMI with passive microwave, infrared and visible measurements available from national and international satellites, and could provide rainfall data series with the temporal resolution of 3-hourly and spatial resolution of 0.25 • × 0.25 • at the coverage area of global 50 • S to 50 • N [28,29]. Numerous studies have validated that TRMM products have acceptable accuracy [28,29,[33][34][35][36][37][38], and good performance has been achieved using TRMM rainfall data in many research fields, including hydrological modeling [33,[39][40][41][42][43][44][45], rainfall characteristics [35,46,47], weather processes [48,49], latent heat flux [50][51][52], extreme precipitation [53,54], and drought/flood monitoring [55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…Michot et al . () have demonstrated that at the daily scale, in most parts of the Amazon Basin, the Tropical Rainfall Measurement Mission (TRMM) 3B42 rainfall estimates provide an exhaustive and quite good precipitation dataset. This enhanced data availability is crucial both to represent the spatial trends in the region and to obtain the relationships that can isolate the effects of deforestation and the interactions between deforestation and large‐scale processes.…”
Section: Introductionmentioning
confidence: 99%